Using microsensor technology to quantify match demands in collegiate women's volleyball - Vlantes, T. G.; Readdy, T. (The Journal of Strength and Conditioning Research, 2017)
The purpose of this study was to quantify internal and external load demands of women's NCAA Division I collegiate volleyball competitions using microsensor technology and session rating of perceived exertion (S-RPE). Eleven collegiate volleyball players wore microsensor technology (Optimeye S5; Catapult Sports, Chicago, IL, USA) during 15 matches played throughout the 2016 season. Parameters examined include player load (PL), high impact PL, percentage of HI PL, explosive efforts (EEs), and jumps. Session rating of perceived exertion was collected 20 minutes postmatch using a modified Borg scale. The relationship between internal and external load was explored, comparing S-RPE data with the microsensor metrics (PL, HI PL, % HI PL, EEs, and jumps). The setter had the greatest mean PL and highest number of jumps of all positions in a 5-1 system, playing all 6 rotations. Playing 4 sets yielded a mean PL increase of 25.1% over 3 sets, whereas playing 5 sets showed a 31.0% increase in PL. A multivariate analysis of variance revealed significant differences (p < 0.01) across all position groups when examining % HI PL and jumps. Cohen's d analysis revealed large (=0.8) effect sizes for these differences. Defensive specialists recorded the greatest mean S-RPE values over all 15 matches (886 ± 384.6). Establishing positional load demands allows coaches, trainers, and strength and conditioning professionals to implement training programs for position-specific demands, creating consistent peak performance, and reducing injury risk.